Impact of the COVID-19 pandemic on the quality of life of older adults - Maricela Carmona-González; Adán Flores-Garnica; Miguel Á. Sánchez-Ramos; María A. Ortiz-Rodríguez; Martha L. Arenas-Ocampo; Luz A. García-Serrano; Brenda H Camacho-Díaz (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background The coronavirus disease 2019 (COVID-19) pandemic has impacted unevenly across nations and population groups. Older adults were considered a high-risk group because of their high susceptibility to infection and potential for clinical complications and death. Long periods of home confinement and social distancing foster changes in daily life that impact the mobility, health and quality of life of older adults. This study aims to assess the quality of life of older adults during the COVID-19 pandemic, adherence to prevention measures, self-perceived impaired mobility, relating to others, daily activities, eating habits and constipation-patterns. # Methods A cross-sectional study with a mixed approach was implemented, with 114 participants completing an online survey. # Findings The participants with poorer quality of life had older age, had less schooling, were unemployed, had no partner, were ill and experienced chronic functional constipation. The intimacy dimension had the lowest score. Mobility, relating to others and activities of daily living were rated by most participants as strongly affected by the pandemic. # Conclusions The COVID-19 pandemic impacted the quality of life of older adults by fostering social isolation and physical inactivity. To ameliorate this, public health interventions are needed.